Control of globin gene expression during development and erythroid differentiation - Stamatoyannopoulos, George (2005)
Extensive studies during the last 30 years have led to considerable understanding of cellular and molecular control of hemoglobin switching. Cell biology studies in the 1970s defined the control of globin genes during erythroid differentiation and led to development of therapies for sickle cell disease. Molecular investigations of the last 20 years have delineated the two basic mechanisms that control globin gene activity during development—autonomous silencing and gene competition. Studies of hemoglobin switching have provided major insights on the control of gene loci by remote regulatory elements. Research in this field has an impact on understanding regulatory mechanisms in general and is of particular importance for eventual development of molecular cures for sickle cell disease and β thalassemia.